2013
DOI: 10.3184/175815512x13528994072997
|View full text |Cite
|
Sign up to set email alerts
|

The Energetic Costs of Nest Building in Birds

Abstract: Parental investment in reproduction is generally limited by the availability of food and so avian life-history research has generally focused on the brood rearing phase, when food requirements are greatest. Only relatively recently has the focus extended to the incubation phase and, even more recently, to the nest-building phase where there is now observational, comparative and experimental evidence that avian nest building is an energetically and temporally expensive activity. This review emphasises that nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 57 publications
(85 reference statements)
4
136
1
3
Order By: Relevance
“…Understanding of the role of nests has increased considerably in recent years, but the nest-building phase of breeding success is relatively understudied (Deeming and Reynolds 2015). Nests represent a major energy investment (Mainwaring and Hartley 2013) and understanding their role, particularly in the light of urbanisation, may help us to understand changes in productivity across habitat gradients and their conservation implications. In addition to finding a broad decline in reproductive output associated with urbanisation, as found elsewhere (Chace and Walsh 2006;Chamberlain et al 2009), we also similarly found heavier nests to be linked with higher reproductive output.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of the role of nests has increased considerably in recent years, but the nest-building phase of breeding success is relatively understudied (Deeming and Reynolds 2015). Nests represent a major energy investment (Mainwaring and Hartley 2013) and understanding their role, particularly in the light of urbanisation, may help us to understand changes in productivity across habitat gradients and their conservation implications. In addition to finding a broad decline in reproductive output associated with urbanisation, as found elsewhere (Chace and Walsh 2006;Chamberlain et al 2009), we also similarly found heavier nests to be linked with higher reproductive output.…”
Section: Discussionmentioning
confidence: 99%
“…For nest building behaviors to be extended phenotypic signals of the building individuals' quality, they must reliably indicate the quality of the builder by being associated with energetic costs (Nager and van Noordwijk, 1992;Maynard Smith and Harper, 2003;Moreno, 2012). There is now evidence that constructing a nest is energetically expensive for birds and that whilst those costs are less substantial than provisioning nestlings or incubating eggs, they are nevertheless far more substantial than they were generally considered to be just a couple of decades ago (e.g., Withers, 1977;Hansell and Ruxton, 2002;Soler et al, 2007;Moreno et al, 2008Moreno et al, , 2010; reviewed by Mainwaring and Hartley, 2013). Thus, nest building behaviors and the design of completed nests may act as sexual signals and there is widespread evidence that they play a role in sexual selection in species where nests are built by males alone (Lens et al, 1994;Evans and Burn, 1996;Gwinner, 1997;Evans, 1997a,b;Soler et al, 2001;de Neve and Soler, 2002;Brouwer and Komdeur, 2004;Polo et al, 2004Polo et al, , 2010Veiga and Polo, 2005;Veiga et al, 2006), by females alone (Moreno et al, 2008(Moreno et al, , 2010 and by both parents (Soler et al, 1998;Sergio et al, 2011).…”
Section: Sexual Selectionmentioning
confidence: 99%
“…Open cup-shaped nests are the most common design [5], having the advantage of relatively simple construction but the disadvantage of potentially exposing eggs, nestlings, and parents to predators and climatic elements [10,11]. A smaller proportion of species build domed nests with roofs, which can take longer to construct but provide greater concealment and insulation [3,5].…”
Section: Introductionmentioning
confidence: 99%